Perancangan Interior Redesain Restoran Bambuden 2 di Makassar - Jaquliene Feby Limewa (Intra, 2017)
Chinese restaurant is one of the most popular places in the community. Rebranding interior design Bambuden 2 restaurant in Makassar is an interior design of a restaurant that presents dominant chinese food, by offering a blend of Oriental character & Elegant Nuance by adding Bar within the restaurant in different scope area. The restaurant is designed is one restaurant that is designed for the middle to top, with a system of waiter service or waitress to tables. The planned facilities include the main dining area, the VIP area, the reception area, the bar area. With the image of a restaurant that is a china restaurant, hence from that concept applied is based on the philosophy of the establishment of Bambuden restaurant itself, the alignment in the blend of Oriental character and Elegant nuance so that the combination of history becomes balanced and harmonious. And also the harmony, a blend of restaurants and bars in the design of this Re-branding. The essence of the whole is to want to show China a more modern atmosphere that is very specific to the history of standing with a more approach towards the blend of concepts and functions.